Cooling capacity of transpulmonary cooling and cold-water immersion after exercise-induced hyperthermia - Adams, W. M.; Butke, E. E.; Lee, J.; Zaplatosch, M. E. (Journal of Athletic Training, 2021)
Context: Cold-water immersion (CWI) may not be feasible in some remote settings, prompting the identification of alternative cooling methods as adjunct treatment modalities for exertional heat stroke (EHS). Objective: To determine the differences in cooling capacities between CWI and the inhalation of cooled air. Design: Randomized controlled clinical trial. Setting: Laboratory. Patients or Other Participants: A total of 12 recreationally active participants (7 men, 5 women; age = 26 ± 4 years, height = 170.6 ± 10.1 cm, mass = 76.0 ± 18.0 kg, body fat = 18.5% ± 9.7%, peak oxygen uptake = 42.7 ± 8.9 mL/kg·min). Intervention(s): After exercise in a hot environment (40°C and 40% relative humidity), participants were randomized to 3 cooling conditions: cooling during passive rest (PASS; control), CWI, and the Polar Breeze thermal rehabilitation machine (PB) with which participants inspired cooled air (22.2°C ± 1.0°C). Main Outcome Measure(s): Rectal temperature (TREC) and heart rate were continuously measured throughout cooling until TREC reached 38.25°C. Results: Cooling rates during CWI (0.18°C·min-1 ± 0.06°C/min) were greater than those during PASS (mean difference [95% CI] of 0.16°C/min [0.13°C/min, 0.19°C/min]; P < .001) and PB (0.15°C/min [0.12°C·min-1, 0.16°C·min-1]; P < .001). Elapsed time to reach a TREC of 38.25°C was also faster with CWI (9.71 ± 3.30 minutes) than PASS (-58.1 minutes [-77.1, -39.9 minutes]; P < .001) and PB (-46.8 minutes [-65.5, -28.2 minutes]; P < .001). Differences in cooling rates and time to reach a TREC of 38.25°C between PASS and PB were not different (P > .05). Conclusions: Transpulmonary cooling via cooled-air inhalation did not promote an optimal cooling rate (>0.15°C·min-1) for the successful treatment of EHS. In remote settings where EHS is a risk, access and use of treatment methods via CWI or cold-water dousing are imperative to ensuring survival.